The petrogenesis of Liberian diamondiferous rocks, Man Craton, West Africa - Ndimande, Njabulo (Department of Geological Sciences, 2023)
Kimberlites and lamproites are ultramafic igneous rocks believed to originate from the convective asthenosphere and sub-continental lithospheric mantle, respectively, however, the genetic link between these rock types is still a debate among researchers. Recently, it has been shown (e.g., in the Dharwar Craton, India) that both kimberlites and lamproites may be derived from the same asthenospheric mantle source. During their ascent to the surface, they assimilate differently metasomatized SCLM material. However, it is not clear if this process applies to all cratonic regions. The Man Craton, West Africa, is a host to diamondiferous rocks that share petrographic and geochemical characteristics with both kimberlites and lamproites, thus not easy to classify. The Camp Alpha (possibly Precambrian in age) and Neoproterozoic-aged Weasua clusters are the selected locations for this study. To further assist with the classification of peculiar West African diamondiferous rocks and evaluate their genetic link and origin, I provide detailed petrography, as well as phlogopite and spinel chemistry, bulk-rock geochemistry (for the Camp Alpha samples) and perovskite chemistry (for the Weasua samples). The Camp Alpha rocks contain abundant macrocrysts of olivine (that are completely altered) and ilmenite occurring in a groundmass that comprises spinel, phlogopite (the samples are phlogopite-poor), perovskite, calcite, serpentine, and rare apatite. Most importantly, there is no evidence of diopside in the Camp Alpha samples. The Camp Alpha phlogopite is enriched in Al2O3 but slightly depleted in FeO and TiO2 and the spinel exhibits a kimberlitic compositional evolution (i.e., trend 1). The bulk-rock trace element ratios Ba/Nb (0.91 - 9.55), La/Nb (0.12 - 1.22; mostly < 1.10) and Ce/Pb (6.77 - 99.2; mostly > 22), fall within the ranges defined by kimberlites. Additionally, primitive mantle normalised trace element patterns are similar to kimberlite patterns (e.g., Rb, K, Sr and P 2 show negative anomalies). As a result of these characteristics, the studied Camp Alpha rocks are classified as kimberlites. A close to parent melt composition of the Camp Alpha kimberlite is provided in this study, based on bulk rock geochemistry. The composition of the estimated melt is similar to that of kimberlite magmas and characterised by low K2O (of 0.80 wt.% relative to 3.63 ± 1.40 wt.% of orangeites for example; reflective of mica-poor nature). The Weasua rocks, in this study, are micaceous (phlogopite-rich) and contain primary groundmass diopside and calcite, which suggests that the studied Weasua rocks represent carbonate-rich olivine lamproites. From the inversion of trace element data for the perovskites using known partition coefficients, the composition of the melt in equilibrium with perovskite at the time of crystallisation is determined. The composition of this Weasua parent melt is similar to that of kimberlite magmas (i.e., similar primitive mantle-normalised trace element patterns, Ba/Nb, Ce/Pb and La/Nb ratios). Whereas the Camp Alpha and Weasua rocks are classified as kimberlite and lamproite, respectively, the trace element composition of the parent melt is similar to that of kimberlite magmas for both cases. This suggests a common asthenospheric magma source for the Camp Alpha kimberlite and Weasua lamproite. En route to the surface, these rock types assimilated differently metasomatized SCLM material (i.e., the Weasua lamproite magma assimilated mica-diopside-rich wall rock). The Camp Alpha kimberlite was shown to be approximately 800 Ma old, similar to the Weasua lamproite. Therefore, the Camp Alpha and Weasua magmas were interpreted to be broadly coeval based on the similarity in age and location, In addition to the Indian Dharwar Craton, the hypothesis that kimberlites and lamproites share a common convective asthenospheric magma source but assimilate differently metasomatized SCLM material en route to the surface is confirmed in the Man Craton, West Africa.